Descriptive Aspects of Injection Drug Users in Iran's National Harm Reduction Program by Methadone Maintenance Treatment - Sharareh Eskandarieh; Ali Nikfarjam; Termeh Tarjoman; Abassali Nasehi; Firoozeh Jafari; Mohammad-Bagher (Tehran University of Medical Sciences, 2013)
Background: The Ministry of Health, Treatment and Medical Education of Iran has recently announced an estimated figure of 200,000 injecting drug users (IDUs). The aim of this study was to pilot a national program using demographics, types of drug abuse and prevalence of blood-borne infections among IDUs.Methods: In order to elicit data on demographics, types of drug abuse and prevalence of blood-borne infections among IDUs, a questionnaire was designed in the Bureau of Mental-Social Health and Addiction in collaboration with Iran's Drug Control Headquarters of the Police Department. Therapeutical alliance of addiction in Shafagh Center was based on Methadone Maintenance Therapy (MMT).Results: Among 402 reported IDUs most of them were male, single and in age range of 20 to 39 years old with 72.7% history of imprisonment. Most of them had elementary and high school education and a history of addiction treatment. The majority were current users of opioid, heroin and crack. The prevalence of blood-borne infections was 65.9% and 18.8% for HCV and HIV/AIDS infections, respectively.Conclusion: Prevention programs about harm reduction, treatment and counseling should include young IDUs as a core focus of their intervention structure